(untitled) (Research, Society and Development, 2023)
The present study aims to investigate the evidence in the literature about the importance and benefits of having a companion during labor. This is an integrative literature review, carried out in the Medical Literature database (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), via the Virtual Health Library and Scientific Electronic Library Online (SCIELO) with health descriptors that included publications from 2015 to 2022. Finally, a full reading was carried out, with each article being filed, leaving a sample of 11 works, which gave rise to two categories semantics. The researched literature highlights the importance of the presence of a companion during labor and how it is widely recognized. The presence of a companion makes a positive contribution at the time of delivery, making it softer and more special, and with the changes made to the health networks, it has shown several benefits, such as physical and emotional support, intermediation and informational support, strengthening of family relationship, among others. The presence of a companion during childbirth is effective, as they actively participate in the birth process, performing support actions and providing bonds, security and countless benefits, contributing to a good evolution of the childbirth. Thus, it is necessary to encourage this intervention with the team and health institutions.